Influence of Sodium Salts on Reduction Roasting of High-Phosphorus Oolitic Iron Ore. (17th November 2022) - Wu, Shichao; Sun, Tichang; Kou, Jue; Li, Xiaohui; Xu, Chengyan; Chen, Zekun
ABSTRACT: The reduction roasting followed by magnetic separation process is considered to be a suitable method to treat the high-phosphorus oolitic iron ore. Currently, the dephosphorization mechanism of additives such as CaCO3, Ca(OH)2, Na2 SO4, and Na2 CO3 on the reduction roasting of the iron ore in which phosphorus occurs in apatite have been thoroughly studied. The effect of sodium salts (Na2 CO3, NaCl and Na2 SO4 ) on reduction roasting and magnetic separation of high-phosphorus oolitic iron ore containing phosphorus in iron oxides was investigated, and the mechanisms of sodium salts were expounded using XRD and SEM-EDS. The results show that the dephosphorization ability of sodium salts was in the order of Na2 SO4 > Na2 CO3 > NaCl>no sodium salts. Na2 CO3 and Na2 SO4 transferred Fe3 PO7 from the iron oxides to nepheline, which upgraded the separation of iron and phosphorus. However, NaCl did not inhibit the reduction of phosphorus in the iron minerals. In addition, Na2 CO3 strengthened the reduction of iron oxides. However, a small amount of wustite failed to be reduced to metallic iron with the addition of NaCl, and troilite and wustite formed hindered the reduction of iron minerals after adding Na2 SO4 .